Taxonomic and nomenclatural changes in Malagasy species of Anhelita Jordan, Lemurisintor Frieser and Sintor Schoenherr (Anthribidae: Coleoptera) - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2025)
Anhelita aphanes Wolfrum, 1959 and Anhelita brevipes Wolfrum, 1961 are here placed in the genus Sintor Schoenherr, 1839. Anhelita distans Wolfrum, 1959 is considered a senior subjective synonym of Lemurisintor longiclava Frieser, 1981, but Lemurisintor Frieser, 1981 is retained as a valid genus. New generic combinations and a new synonymy are proposed as follows: Sintor aphanes (Wolfrum, 1959) comb. nov., Sintor brevipes (Wolfrum, 1961) comb. nov., Lemurisintor distans (Wolfrum, 1959) comb. nov. (= Lemurisintor longiclava Frieser, 1981 syn. nov.). Lectotypes are designated for Anhelita lineata Jordan, 1895 and Anhelita unicarinata Wolfrum, 1959. A key to the previously confused genera Anhelita Jordan, 1895, Lemurisintor and Sintor Schoenherr, 1839, and colour macro-photographs of the types of Anhelita and Lemurisintor, and all Madagascan species of Sintor, are provided. Male and female terminalia are described for a representative species of each of Anhelita and Sintor. New data on the distribution of species of these three genera are presented.